Overview of Hemoglobin Levels Using the Cyanmethemoglobin Method in Lipidemia Specimens at the East Kalimantan Provincial Health Laboratory - Muhammad Rio Kharismawan; Supri Hartini; I gede Andika Sukarya (PT. Edukasi Ahmad Kirang, 2026)
Background: Hemoglobin level measurement using the cyanmethemoglobin method is affected by lipemic samples. Lipemic serum, caused by lipoprotein particles such as chylomicrons, VLDL, and triglycerides, creates chromophoric interference in photometric analysis, affecting wavelength readings and causing light scattering due to lipid particles. Methods: An observational analytic study using a total sampling technique was conducted at the East Kalimantan Provincial Health Laboratory during August–September 2024. A total of 30 lipemic specimens were included, collected from patients undergoing routine blood examination with cholesterol levels >200 mg/dL. Data were obtained from secondary medical records. Results: Of 30 lipemic samples, 28 samples (93%) showed hemoglobin levels within the normal range and 2 samples (7%) were below normal. The minimum hemoglobin value was 12.0 g/dL, maximum was 15.7 g/dL, and the mean was 13.7 g/dL. Regarding cholesterol levels, 22 samples (73%) had cholesterol of 201–250 mg/dL and 8 samples (27%) had cholesterol of 251–300 mg/dL. Conclusion: Hemoglobin measurement in lipemic serum using the cyanmethemoglobin method can serve as an accurate reference. The average results showed no values outside the normal range. The two samples below normal may be attributable to unknown confounding variables such as dietary habits, smoking behavior, and age.